การวิเคราะห์ค่าความร้อนของใบไม้เพื่อทำนายความรุนแรงของไฟป่าในป่าเต็งรัง - ปัญญากร ดีเรือน (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The deposition of dried leaves on forest floor in dry season of Dipterocarp forest causes a forest fire frequently. Therefore, this research aims to find out a heat content and the burning characteristic of Dipterocarp forest fuels which are Teng leaves, Rang leaves, Pluang leaves and Hiang leaves. The data from this study will be used as an additional information for fuel management plan and reducing the risk of fire intensity. This research was conducted by using 2 methods to find heating value and burning characteristics following ASTM D3180 and ASTM E2058 standards. There were 4 types of fuels including Teng leaves, Rang leaves, Pluang leaves and Hiang leaves. The fuels were divided into 3 groups in order of their quantity from 3 leaves, 4 leaves and 5 leaves. The results show that the higher heating values were 5,356 kcal/kg, 4,874 kcal/kg, 4,553 kcal/kg and 4,557 kcal/kg of Teng leaves, Rang leaves, Hiang leaves and Pluang leaves, respectively. Ignition times were 45.8 sec, 50.6 sec, 55.5 sec and 84.5 sec of Hiang leaves, Rang leaves, Teng leaves and Pluang leaves, respectively. The maximum flame heights were 18.8 cm, 18.4 cm, 17.8 cm and 6.9 cm of Rang leaves, Teng leaves, Pluang leaves and Hiang leaves, respectively. Flame temperatures were 525.8 °C, 509.1 °C, 498.3 °C and 320.8 °C of Rang leaves, Teng leaves, Pluang leaves and Hiang leaves, respectively. Mass loss rates were 0.006442 g/sec, 0.006385 g/sec, 0.004485 g/sec and 0.004509 g/sec of Rang leaves, Teng leaves, Pluang leaves and Hiang leaves, respectively.